Profil Kadar Gula Darah Lansia Pasca Pelaksanaan Senam Lansia Berbasis Sekolah Lansia - Novita Dewi; Neni Maemunah; Ronasari Mahaji Putri (Jurnal Akademika Baiturrahim Jambi, 2026)
Increased blood glucose levels in older adults are associated with the aging process, which is characterized by decreased insulin sensitivity and reduced skeletal muscle mass and function, leading to suboptimal glucose utilization. Elderly exercise is a structured physical activity that can serve as a non-pharmacological intervention to support metabolic regulation in older populations. This study aimed to describe the profile of blood glucose levels among older adults after participating in an elderly exercise program based on a community elderly school. This study employed a pre-experimental design with a one-shot case study approach involving 15 respondents aged 60–76 years at the SMART “Teratai” Elderly School in Bandungrejosarisari, Sukun, Malang. The instruments used included an observation sheet and a random blood glucose measurement conducted once after the exercise session. Data were analyzed descriptively, including mean, median, standard deviation, minimum, and maximum values. The results showed that the median blood glucose level after the exercise was 107 mg/dL, with a range from 52 mg/dL to 326 mg/dL. Most respondents were female (93.3%) and aged between 60–75 years (86.7%). These findings indicate that the majority of older adults had relatively controlled blood glucose levels after participating in the exercise program. In conclusion, elderly exercise programs conducted through elderly schools have the potential to serve as a promotive strategy in maintaining metabolic health among older adults.